Tingkat Kepatuhan Penggunaan Obat Antihipertensi pada Pasien Hipertensi Rawat Jalan di Puskesmas Banyumas Kabupten Pringsewu - Intan Ainur Rokhimah; Annisa Primadiamanti; Martianus Perangin Angin (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Background: WHO shows that approximately 1.13 billion people in the world suffer from hypertension. The percentage of non-adherence to taking medication for hypertension sufferers in Indonesia is estimated to be 32.3%. Objectif : This study aims to determine the level of patient compliance in the use of antihypertensive drugs in outpatient hypertension patients at the Banyumas Public Health Center, Pringsewu Regency. Methods : how the study was performed and statistical tests used. how the study was performed and statistical tests used how the study was performed and statistical tests used how the study was performed and statistical tests used how the study was performed and statistical tests used. Results: The results showed that the frequency of adherence to medication was categorized into 3 categories, namely compliance, moderate, and low. The level of adherence to taking medication for hypertension sufferers at the Banyumas Health Center is 9% with high adherence, 38% moderate adherence, 53% low adherence. Conclusion : The level of adherence to the use of antihypertensive drugs in hypertensive patients who seek treatment at the Banyumas Public Health Center is mostly included in the low level of adherence. The results of Chi Square showed that there were no characteristics of the research subjects that affected the compliance of hypertension patients at the Banyumas Public Health Center, Pringsewu Regency (P 0.05).Keywords : Hypertension, Compliance, MMAS-8